Montage. The opening speech of Kyra László glass artist’s exhibition ”Montage” - Ficzek, Ferenc (ARTCADIA, 2024)
”I’m convinced that it’s materials that choose artists and not artists who choose materials. I love it that I and glass are ‘co-creators’, that there is an unplannable, random coefficient when I’m working with this material.” – says Kyra László glass artist, whose glass sculptures were on display in the culture house of Hosszúhetény in September 2024.László graduated in glass art from the Hungarian University of Arts and Design in 2003, is a member of the Hungarian Glass Art Society and a regular participant of international glass symposia and exhibitions. She allows the transparency of glass to prevail in her art, and the material is the dominant feature in her monochrome or limited colour works. She works mainly with flat glass which she shapes using fusing techniques: she is interested in the layering of the material, experimenting with spatial relationships, and her sculptures often deal with the theme of balance, playing with the question of the outside-inside and the contrasts between the malleability and rigidity of glass. The artist’s exhibition was opened by Ferenc Ficzek, whose text is published here.
Keywords: Kyra László; glass; exhibition; transparency; space; fusing